(untitled) (Research, Society and Development, 2020)
The present study aimed to verify the association between the sedentary behavior and the main disorders in oral health through an integrative review of the literature. Structured searches were carried out in the PUBMED, SCOPUS and SCIELO databases to find the original research studies. An electronic form was used to extract data about author, year, population, measures of evaluation of the outcomes of interest, main results and conclusions of the authors. Of the 216 studies identified in the databases, 12 included the inclusion criteria. Of these, 09 pointed out an association between sedentary behavior and oral health, indicating that such behavior has a negative impact on the oral health of the individuals. Three articles did not relate sedentarism as a risk factor for oral health disorders. Although most studies point to a possible association, there is still needed more well-designed and with longer follow-up studies to confirm sedentary behavior as a risk factor for the development of oral diseases. In the perspective of a dental approach to risk factors in common with systemic diseases, it is advised that clinicians should be aware of the lifestyle adopted by their patients in order to guide them in choosing a healthy lifestyle.